Enhanced physical properties of the anodic TiO2 nanotubes via proper anodization time - Zahra Jedi-soltanabadi; Negin Pishkar; Mahmood Ghoranneviss (Journal of Theoretical and Applied Physics)
Abstract Vertically aligned titanium dioxide (TiO2) nanotubes were synthesized by electrochemical anodic oxidation in an electrolyte solution containing 0.45 wt% ammonium fluoride (NH4F) and 2 vol% deionized water at constant potential (70 V) for various anodization time at the room temperature. The influence of the anodization time on the morphology and optical properties of the anodic TiO2 nanotubes have been studied. Field emission scanning electron microscopy results revealed that the anodic TiO2 nanotube morphology extremely depends on the anodization time. It was observed that by increasing anodization time, length of the anodic TiO2 nanotubes increased and nanotubes destroyed at the top of the tubes. After a long time of anodization process (9 h), nanotubes completely destroyed. Photoluminescence measurements showed that the anodic TiO2 nanotube band gap energy depends on the anodic TiO2 nanotube morphology. The anodic TiO2 nanotubes without any damage had a minimum band gap energy (2.9 eV).